Global cluster analysis and network visualization in organoids in cancer research: a scientometric mapping from 1991 to 2021 - Tan, Shunshun; Deng, Jiali; Deng, Haobin; Lu, Lijun; Qin, Zhenzhe; Liu, Yu; Tang, Lifeng; Li, Zhonghua (Frontiers in Oncology, 2023)
Objective In the last three decades, there has been a surge in research on cancer organoids using 3D culture technologies, which has resulted in the development of physiological human cancer models. This study aims to provide an overview of the global trends and frontiers in research on cancer organoids. Methods A total of 3189 publications on organoids in cancer research from 1991 to 2021 were collected from the Science Citation Index-Expanded (SCIE) of Web of Science (WoS). Bibliometric methods such as the R package “Bibliometrix,” Citespace, and VOS viewer software were employed to investigate and visualize bibliographic coupling, co-citation, co-authorship, and co-occurrence trends, as well as publication trends in the field of organoids in cancer research. Results From 1991 to 2021, there has been a significant increase in publications on cancer organoids, with most articles being from North America, Eastern Asia, and Western Europe. The USA had the highest number of publications, citations, prolific authors, and research funding globally. Cancers was the journal with the most publications, while Nature had the best total link strength. Harvard University were the most contributive institutions. The global research in this field could be classified into five clusters: chemotherapy study, organoids for drug screening, different models, molecular mechanism study, and organoid construction. These areas are expected to remain hotspots for future research. Conclusions The number of publications on organoids in cancer research is expected to increase based on current global trends.